2018
DOI: 10.3390/s18113971
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Evaluation of Broadband Photoacoustic Spectroscopy in the Infrared with an Optical Parametric Oscillator

Abstract: We evaluate the spectral resolution and the detection thresholds achievable for a photoacoustic spectroscopy (PAS) system in the broadband infrared wavelength region 32700.166667emnm≲λ≲35300.166667emnm driven by a continuous wave optical parametric oscillator (OPO) with P¯-0.166667em≈-0.166667em1.260.166667emnormalW. The absorption spectra, IPAS(λnormali), for diluted propane, ethane and methane test gases at low concentrations (c∼1000.166667emppm) were measured for ∼1350 discrete wavelengths λnormali. The IPA… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Among these, Optical parametric oscillators (OPOs) and super‐continuum (SC) lasers have emerged as two of the most promising broad‐spectrum light sources. OPOs use high‐quality nonlinear crystals to enable parametric amplification of high‐power pump laser sources, 96 which can provide superior spectral resolution, high output power, and broad tunable wavelengths (2–14 μm). Lamard L et al demonstrated a single longitudinal mode pulsed OPO laser 69 .…”
Section: Laser‐based Pas Technologymentioning
confidence: 99%
“…Among these, Optical parametric oscillators (OPOs) and super‐continuum (SC) lasers have emerged as two of the most promising broad‐spectrum light sources. OPOs use high‐quality nonlinear crystals to enable parametric amplification of high‐power pump laser sources, 96 which can provide superior spectral resolution, high output power, and broad tunable wavelengths (2–14 μm). Lamard L et al demonstrated a single longitudinal mode pulsed OPO laser 69 .…”
Section: Laser‐based Pas Technologymentioning
confidence: 99%
“…A growing interest in PAS for the 2.5-5 µm region is represented by cw periodically poled lithium niobate optical parametric oscillators (PPLN-OPOs) at high power (several watts) level and narrow linewidth. OPOs are pumped by high power lasers and its outstanding features are wide-range wavelength tunability of the emitted radiation with high and stable output power levels, and an exceptional beam quality and these characteristics make OPOs very valuable for laser spectroscopy [65][66][67].…”
Section: Laser Sourcesmentioning
confidence: 99%
“…In that case, the absorption bands will consist of well separated lines that usually allow discriminating the absorption features from different components and obtaining independent calibration curves for each species. When broadband absorptions related to more structured molecules overlap each other, several algorithms based on multiple linear regressions, partial least squares or multivariate analysis can be implemented to quantify the concentration of each gas [18][19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%